Antioxidant, anti-inflammatory and cytotoxicity of Phaleria macrocarpa (Boerl.) Scheff fruit - Hendra, Rudi; Ahmad, Syahida; Oskoueian, Ehsan; Md.Sukari, Mohd. Aspollah; Abd. Shukor, Mohd. Yunus (BioMed Central, 2011)
Background Phaleria macrocarpa (Scheff.) Boerl (Thymelaceae) originates from Papua Island, Indonesia and grows in tropical areas. The different parts of the fruit of P. macrocarpa were evaluated for antioxidant, anti-inflammatory, and cytotoxic activities. Methods Phaleria macrocarpa fruit were divided into pericarp, mesocarp and seed. All parts of the fruit were reflux extracted with methanol. The antioxidant activity of the extracts were characterized in various in vitro model systems such as FTC, TBA, DPPH radical, reducing power and NO radical. Anti-inflammatory assays were done by using NO production by macrophage RAW 264.7 cell lines induced by LPS/IFN-γ and cytotoxic activities were determined by using several cancer cell lines and one normal cell line Results The results showed that different parts (pericarp, mesocarp, and seed) of Phaleria macrocarpa fruit contain various amount of total phenolic (59.2 ± 0.04, 60.5 ± 0.17, 47.7 ± 1.04 mg gallic acid equivalent/g DW) and flavonoid compounds (161.3 ± 1.58, 131.7 ± 1.66, 35.9 ± 2.47 mg rutin equivalent/g DW). Pericarp and mesocarp showed high antioxidant activities by using DPPH (71.97%, 62.41%), ferric reducing antioxidant power (92.35%, 78.78%) and NO scavenging activity (65.68%, 53.45%). Ferric thiocyanate and thiobarbituric acid tests showed appreciable antioxidant activity in the percentage hydroperoxides inhibitory activity from pericarp and mesocarp in the last day of the assay. Similarly, the pericarp and mesocarp inhibited inducible nitric oxide synthesis with values of 63.4 ± 1.4% and 69.5 ± 1.4% in macrophage RAW 264.7 cell lines induced by LPS/IFN-γ indicating their notable anti-inflammatory potential. Cytotoxic activities against HT-29, MCF-7, HeLa and Chang cell lines were observed in all parts. Conclusions These results indicated the possible application of P. macrocarpa fruit as a source of bioactive compounds, potent as an antioxidant, anti inflammatory and cytotoxic agents.